Self-Control within a Muslim Ideological Surround: Empirical Translation Schemes and the Adjustment of Muslim Seminarians in Iran - Ghorbani, Nima (Research in the social scientific study of religion, 2016)
Associated with the Ideological Surround Model of the relationship between religion and the social sciences, empirical translation schemes are a procedure for converting psychological measures into functionally equivalent religious constructs. In a sample of Muslim seminarians in Iran, this procedure transformed the Brief Self-Control Scale as a measure relevant to a non-religious Darwinian perspective into a language more reflective of a Muslim ideological surround. Brief and Muslim Self-Control scales correlated positively. Each also predicted the religious adjustment of a stronger Intrinsic and Extrinsic Personal Religious Orientation and the psychological adjustment of greater Self-Esteem and Satisfaction with Life and of lower Perceived Stress, Depression, and Anxiety. Correlation, multiple regression, and mediation analyses identified Darwinian and Muslim perspectives on self-control as largely compatible. This investigation most broadly illustrated the need for a post-postmodern sensitivity to immanent social scientific, transcendent religious, and dialogical ideological surrounds.